2015
DOI: 10.1016/j.celrep.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

GPR124 Functions as a WNT7-Specific Coactivator of Canonical β-Catenin Signaling

Abstract: SUMMARY G-protein coupled receptor 124 (GPR124) is an orphan receptor in the adhesion family of GPCRs and previous global or endothelial-specific disruption of Gpr124 in mice led to defective CNS angiogenesis and blood brain barriergenesis. Similar developmental defects were observed following dual deletion of Wnt7a/Wnt7b or deletion of β-catenin in endothelial cells, suggesting a possible relationship between GPR124 and canonical WNT signaling. Here, we show using in vitro reporter assays, mutation analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
138
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 23 publications
7
138
0
2
Order By: Relevance
“…The mechanism of synergistic signaling from WNT1 and WNT7B was examined in depth. Synergy required both FZD5 and FZD8, as well as the recently identified WNT7A and WNT7B co-receptors GPR124 and RECK (Posokhova et al, 2015;Zhou and Nathans, 2014). The WNT7B-GPR124 interaction markedly stimulated K49 acetylation of β-catenin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of synergistic signaling from WNT1 and WNT7B was examined in depth. Synergy required both FZD5 and FZD8, as well as the recently identified WNT7A and WNT7B co-receptors GPR124 and RECK (Posokhova et al, 2015;Zhou and Nathans, 2014). The WNT7B-GPR124 interaction markedly stimulated K49 acetylation of β-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant Wnt signaling is associated with many pathological conditions (Clevers and Nusse, 2012). Nineteen distinct genes in the human genome encode Wnt ligands, which bind to a variety of receptors including ten frizzled proteins (FZDs) and the coreceptors low-density lipoprotein receptor-related protein 5 and 6 (LRP5/6), as well as an increasing number of alternative receptors and co-receptors including the single transmembrane receptors RYK, ROR1/2, PTK7 and GPR124 (also known as ADGRA2) to trigger various downstream signaling pathways (MacDonald et al, 2009;Niehrs, 2012;Posokhova et al, 2015;Zhou and Nathans, 2014). Many Wnt ligands can stimulate β-catenin-induced gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Along with Reck, it has been shown to control DRG formation by activating Wnt signaling in neural crest-derived sox10:mRFP + ganglion cells (Vanhollebeke et al, 2015). In addition, Adgra2 and Reck function as essential regulators of brain vascular development by promoting Wnt/ β-catenin signaling in cerebrovascular endothelial cells (ECs) (Posokhova et al, 2015;Ulrich et al, 2016;Vanhollebeke et al, 2015;Zhou and Nathans, 2014). While the pivotal role of these proteins in cerebrovascular development is established both in the zebrafish and the mouse model (Anderson et al, 2011;Cullen et al, 2011;de Almeida et al, 2015;Kuhnert et al, 2010;Noda et al, 2016;Posokhova et al, 2015;Ulrich et al, 2016;Vanhollebeke et al, 2015;Zhou and Nathans, 2014), the molecular mechanisms underlying their activation and signal transduction remain to be determined.…”
mentioning
confidence: 99%
“…Adgra2 is a newly discovered Wnt7-specific co-activator of Wnt/β-catenin signaling (Posokhova et al, 2015;Vanhollebeke et al, 2015;Zhou and Nathans, 2014). Along with Reck, it has been shown to control DRG formation by activating Wnt signaling in neural crest-derived sox10:mRFP + ganglion cells (Vanhollebeke et al, 2015).…”
mentioning
confidence: 99%
“…Meanwhile, it is also found that the total survival rate of GPR124 high expression group is somehow lower than the one of low expression group. This shows that the expression of GPR124 can promote the development of cancer as well as affect the prognosis (25).…”
Section: Discussionmentioning
confidence: 99%